Site-specific concentrations of carotenoids in adipose tissue: relations with dietary and serum carotenoid concentrations in healthy adults - Chung, Hae-Yun; Ferreira, Ana Lúcia dos Anjos [UNESP]; Epstein, Susanna; Paiva, Sergio Alberto Rupp de [UNESP]; Castaneda-Sceppa, Carmen; Johnson, Elizabeth J. (Amer Soc Clinical Nutrition, 2009)
Background: Dietary carotenoids are related to a decreased risk of certain diseases. Serum and adipose tissue carotenoid concentrations are used as biomarkers of intake.Objectives: The objectives of this study were to evaluate site-specific concentrations of carotenoids in adipose tissue and to examine relations between carotenoid concentrations in the diet, serum, and adipose tissue.Design: Healthy adults (12 women and 13 men) participated in this cross-sectional study. Dietary carotenoids over the past year were assessed with a food-frequency questionnaire. Serum and adipose tissue biopsy samples were collected from the abdomen, buttock, and inner thigh for the measurement of carotenoids by HPLC.Results: Many adipose carotenoids were inversely related to percentage body fat, although lycopene was the only carotenoid inversely correlated with all 3 sites. Most of the carotenoids were significantly higher in the abdominal adipose tissue than in the thigh (P < 0.05). Concentrations of alpha-carotene, beta-carotene, 5-cis-lycopene, and total carotenoids were significantly higher in the buttocks than in the thigh (P < 0.05). Concentrations of alpha-carotene, cis-lycopene, and lutein (with or without zeaxanthin) were significantly higher in the abdomen than in the buttocks (P < 0.05). Dietary intake was significantly correlated with serum concentrations of alpha-carotene, beta-carotene, beta-cryptoxanthin, and total carotenoids. Carotenoid intake was significantly correlated with adipose tissue concentrations of alpha-carotene, beta-carotene, beta-cryptoxanthin, cis-lycopene, and total carotenoids (P < 0.05) but varied by site. of all the adipose tissue sites evaluated, the abdomen showed the strongest correlation with long-term dietary carotenoid intakes and with serum (indicator of short-term intake) for most carotenoids.Conclusions: Body fat may influence the tissue distribution of carotenoids. Abdominal adipose tissue carotenoid concentrations may be a useful indicator of carotenoid status. Am J Clin Nutr 2009;90:533-9.